Upaya Peningkatan Hasil Belajar IPA Materi Zat dan Perubahannya dengan Metode Eksperimen Pada Siswa Kelas V Sekolah Dasar Negeri 2 Kaliwulu Kecamatan Plered - Shulkhah Shulkhah; Lusiani Lusiani; Febriyansyah Febriyansyah (EduBase : Journal of Basic Education, 2021)
The effectiveness of learning that boils down to mastery of learning material to the maximum in children is more determined by the ability of teachers to package a learning activity. If all teachers realize that meaningful learning processes and optimal results affect the ability of children to deal with problems in the future, then every time a teacher plans to prepare a lesson plan will try to create a scenario that can arouse student motivation. The purpose of this paper is "To find out the increase in student learning outcomes in matter substances and their changes through the experimental method". Research uses classroom action research through the preparatory stage, compiling an action plan and a class action research plan held in the Natural Sciences learning process. Data collection techniques that researchers do in class action research is to use test techniques and observation techniques. The data used to measure learning outcomes on subject matter and their changes through the experimental method are data from the results of the first cycle test, and the second cycle. The results of these tests are numbers, then the data analysis used is qualitative data, and the observational data as quantitative data. The data is used by researchers to determine the success of learning the first cycle and second cycle. The results of the study are that: Obtaining the value of the percentage of students in learning cycle 1 of 61.86% According to the Minimum Mastery Criteria (KKM) of 70, the results of improvement in learning cycle 1 need to be followed up by carrying out activities to improve learning cycle 2. Students feel happy in participating in learning activities , so that students 'mastery of the material increases, as evidenced by the increase in teacher activity reaching 88.75% (very good), the motivation of students to participate in learning reached 96% (excellent) and the acquisition of the percentage of students' value in improving learning cycle 3 is 81.86%. Thus, learning science with material substances and their changes is said to have succeeded in mastering the material. The use of experimental methods is proven to be able to improve students' ability to improve science learning outcomes on the subject matter of matter and its changes. The acquisition of student grades above the minimum completeness criteria is 70. Abstrak Efektifitas pembelajaran yang bermuara pada penguasaan materi pembelajaran secara maksimal pada anak lebih banyak ditentukan oleh kemampuan guru dalam mengemas sebuah aktivitas pembelajaran. Jika semua guru menyadari bahwa proses pembelajaran yang bermakna dan hasil yang optimal berpengaruh pada kemampuan anak menghadapi masalah di masa depan, maka sudah seharusnya setiap kali mempersiapkan sebuah rencana pembelajaran guru akan berusaha menciptakan sebuah skenario yang mampu membangkitkan motivasi siswa.Tujuan penulisan ini adalah â€œUntuk mengetahui peningkatan hasil belajar siswa dalam materi zat dan perubahannya melalui metode eksperimenâ€.Penelitian menggunakan penelitian tindakan kelas melalui tahap persiapan, menyusun rencana tindakan dan rencana penelitian tindakan kelas yang diselenggarakan dalam proses pembelajaran Ilmu Pengetahuan Alam.Teknik pengumpulan data yang peneliti lakukan pada Penelitian tindakan kelas yaitu dengan menggunakan teknik tes dan teknik observasi. Data yang digunakan untuk mengukur hasil belajar terhadap materi pokok zat dan perubahannya melalui metode eksperimen adalah data dari hasil tes siklus pertama, dan siklus kedua. Hasil tes tersebut adalah angka, maka analisa data yang digunakan adalah data kualitatif, dan data hasil observasi/pengamatan sebagai data kuantitatif. Data tersebut digunakan peneliti untuk mengetahui keberhasilan pembelajaran siklus pertama dan siklus kedua. Hasil penelitian adalah bahwa: Perolehan nilai prosentase siswa pada pembelajaran siklus 1 sebesar 61,86% Sesuai Kriteria Ketuntasan Minimal (KKM) sebesar 70 maka hasil perbaikan pembelajaran siklus 1 perlu ditindaklanjuti dengan melakukan kegiatan perbaikan pembelajaran siklus 2.Siswa merasa senang dalam mengikuti kegiatan pembelajaran, sehingga penguasaan siswa pada materi meningkat, terbukti dengan meningkatnya aktivitas guru mencapai 88,75% (baik sekali), motivasi siswa mengikuti pembelajaran mencapai 96% (baik sekali) dan perolehan prosentasi nilai siswa pada perbaikan pembelajaran siklus 3 yaitu 81,86%. Dengan demikian, pembelajaran IPA dengan materi zat dan perubahannya dinyatakan telah berhasil menguasai materi. Penggunaan metode eksperimen terbukti dapat meningkatkan kemampuan siswa dalam meningkatkan hasil belajar IPA pada materi pokok zat dan perubahannya. Adapun perolehan nilai siswa di atas standar kriteria ketuntasan minimal yaitu 70.